The resource-seeking internationalization process of a nongovernmental organization - Paula Porto; Angela da Rocha (BAR: Brazilian Administration Review, 2021)
This paper aims at investigating the resource-seeking internationalization process of an international nongovernmental organization (INGO) from the process point of view. INGOs have received scant attention in the international business literature, despite their relevance in almost every aspect of aid and development and as actors of global governance. The research question addresses the issue of whether or not INGOs can follow a path similar to business firms in their internationalization process. The study departs from two different theoretical perspectives — the Uppsala model and the born global perspective — to study the case of the NGO Médecins Sans Frontières (Doctors Without Borders), an international, private, nonprofit, member-based organization. We identify three stages in the resource-seeking internationalization process of the NGO, which present similarities with that of business organizations. The study contributes to the IB literature by revealing key aspects of the internationalization trajectory of an NGO to raise funds and recruit volunteers in advanced and emerging economies with the purpose of employing these resources to support its emergency assistance activities in less developed countries, and to the literature on INGOs in exploring the issue of resource-seeking internationalization.